2004
DOI: 10.1007/s00464-003-8176-z
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative validity of the Minimally Invasive Surgical Trainer in Virtual Reality (MIST-VR) using criteria levels based on expert performance

Abstract: The MIST-VR system is capable of evaluating the psychomotor skills necessary in laparoscopic surgery and discriminating between experts and novices. Furthermore, although some novices improved their skills quickly, a subset had difficulty acquiring the psychomotor skills. The MIST-VR may be useful in identifying that subset of novices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
74
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(83 citation statements)
references
References 17 publications
(35 reference statements)
7
74
1
1
Order By: Relevance
“…Rapid ''flooring'' of the error score is also seen in other studies [6]. Apparently, indeed controlled instrument movements avoiding collisions are aptitudes mastered rapidly.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Rapid ''flooring'' of the error score is also seen in other studies [6]. Apparently, indeed controlled instrument movements avoiding collisions are aptitudes mastered rapidly.…”
Section: Discussionsupporting
confidence: 76%
“…Strong discriminative ability between levels of experience for time and path length parameters also is observed with other simulators [4,6,11,[13][14][15]17]. The results in this study suggest that the tasks mimic psychomotor skills needed for endoscopic surgery.…”
Section: Discussionsupporting
confidence: 66%
“…2 Educators have also expressed concern that new duty hour restrictions limit clinical exposure to critically ill patients and represent an additional challenge to resident competence. 3,4 Simulation-based education improves trainees' knowledge and skills in areas such as invasive procedures, [5][6][7][8][9] communication skills, 10 and management of medical emergencies. [11][12][13] Simulation-based interventions in the ICU setting have also shown promise in promoting resident confidence 14 and critical care skills.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the difficulties in performing endoscopy such as disturbed hand-eye coordination, visual feedback from a threedimensional (3D) environment to a 2D monitor, and working with long instruments, the surgeon has to practice. Several studies have shown that virtual reality (VR) simulators are useful and valid tools for training psychomotor skills such as hand-eye coordination [5,6,8,9,13,14]. Currently, the training of these skills generally is undertaken in structured courses during 1 or 2 days and continues inside the clinic.…”
mentioning
confidence: 99%